1999
DOI: 10.1152/ajprenal.1999.276.1.f129
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction stimulates COX-2 expression in bladder smooth muscle cells via increased mechanical stretch

Abstract: Studies were performed to investigate the regulatory mechanism of bladder cyclooxygenase-2 (COX-2) expression after outlet obstruction. In situ hybridization of murine bladder tissues using COX-2-specific riboprobes demonstrated that COX-2 expression was induced predominantly in the bladder smooth muscle cells after outlet obstruction. To study the effect of increased mechanical stretch on COX isoform expression, cultured rat bladder smooth muscle cells were grown on silicone elastomer-bottomed plates coated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
3
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 28 publications
8
67
3
4
Order By: Relevance
“…It has been reported that several COX inhibitors also act as PPARγ agonists (27,28). However, the concentration of NS-398 (10 µM) used in this study has been used before (for example, 5 -50 µM) for specific inhibition of COX-2 (8,19,29). In fact, we did not observe any apparent effect of NS-398, when used during the induction period, on the triglyceride accumulation in the maturation period (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…It has been reported that several COX inhibitors also act as PPARγ agonists (27,28). However, the concentration of NS-398 (10 µM) used in this study has been used before (for example, 5 -50 µM) for specific inhibition of COX-2 (8,19,29). In fact, we did not observe any apparent effect of NS-398, when used during the induction period, on the triglyceride accumulation in the maturation period (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…An experimental model of BOO was established as described in Materials and Methods, and after 24 h, expression of endogenous indicators for individual stress was evaluated by northern blot analysis. The indicators used were COX-2 for mechanical stress, 17 GAPDH and VEGF for hypoxic stress [18][19][20] and GRP78 and CHOP for ER stress. 7,21 Northern blot analysis showed that, compared with untreated and sham-operated rats, rats subjected to BOO exhibited induction of COX-2 (Figure 1a), GAPDH and VEGF (Figure 1b) in the bladders.…”
Section: Induction Of Mechanical Stress Hypoxic Stress and Er Stressmentioning
confidence: 99%
“…Baskin and colleagues (3,4) have reported an increase in transforming growth factor (TGF)-␤2, TGF-␤3, and TGF-␣ in bladders subjected to partial urethral outlet obstruction and correlate such increases with excessive deposition of extracellular matrix proteins. Studies in various animal models and in humans showed that hypertrophied obstructed bladders contain significantly more insulin-like growth factor I (IGF-I) and cyclooxygenase-2 than normal bladders (1,11,43). Other studies emphasized the role of the renin-angiotensin system and inducible nitric oxide synthase in the early responses of the bladder to the outlet obstruction (5,12).…”
mentioning
confidence: 99%